The avian influenza virus nucleoprotein gene and a specific constellation of avian and human virus polymerase genes each specify attenuation of avian-human influenza A/Pintail/79 reassortant viruses for monkeys. - Snyder, M H (1987)
Reassortant viruses which possessed the hemagglutinin and neuraminidase genes of wild-type human influenza A viruses and the remaining six RNA segments (internal genes) of the avian A/Pintail/Alberta/119/79 (H4N6) virus were previously found to be attenuated in humans. To study the genetic basis of this attenuation, we isolated influenza A/Pintail/79 X A/Washington/897/80 reassortant viruses which contained human influenza virus H3N2 surface glycoprotein genes and various combinations of avian or human influenza virus internal genes. Twenty-four reassortant viruses were isolated and first evaluated for infectivity in avian (primary chick kidney [PCK]) and mammalian (Madin-Darby canine kidney [MDCK]) tissue culture lines. Reassortant viruses with two specific constellations of viral polymerase genes exhibited a significant host range restriction of replication in mammalian (MDCK) tissue culture compared with that in avian (PCK) tissue culture. The viral polymerase genotype PB2-avian (A) virus, PB1-A virus, and PA-human (H) virus was associated with a 900-fold restriction, while the viral polymerase genotype PB2-H, PB1-A, and PA-H was associated with an 80,000-fold restriction of replication in MDCK compared with that in PCK. Fifteen reassortant viruses were subsequently evaluated for their level of replication in the respiratory tract of squirrel monkeys, and two genetic determinants of attenuation were identified. First, reassortant viruses which possessed the avian influenza virus nucleoprotein gene were as restricted in replication as a virus which possessed all six internal genes of the avian influenza A virus parent, indicating that the nucleoprotein gene is the major determinant of attenuation of avian-human A/Pintail/79 reassortant viruses for monkeys. Second, reassortant viruses which possessed the viral polymerase gene constellation of PB2-H, PB1-A, and PA-H, which was associated with the greater degree of host range restriction in vitro, were highly restricted in replication in monkeys. Since the avian-human influenza reassortant viruses which expressed either mode of attenuation in monkeys replicated to high titer in eggs and in PCK tissue culture, their failure to replicate efficiently in the respiratory epithelium of primates must be due to the failure of viral factors to interact with primate host cell factors. The implications of these findings for the development of live-virus vaccines and for the evolution of influenza A viruses in nature are discussed.